Front Office Management Implementation at Mandaya Karawang Hospital Based on Hospitality Principles - Leihitu, Izaak Samuel; Gunawijaya, Jajang; Ariani, Vitria (Institut Pariwisata Trisakti, 2019)
Hospitals are increasingly needed by the public. The increasing demand makes hospital growth increase. An increase of 154.7% occurred between 1997 and 2017. However, the increase in hospitals was not in line with improved services. Many complaints come from patients to the services provided by the hospital. This research is a study using a combination of qualitative methods and quantitative methods. Data collection techniques in qualitative methods were by observation and interviews with informants who worked at Mandaya Hospital Karawang and Resinda Hotel Karawang managed by Padma Hotels as a comparison. Data collection on quantitative methods is by distributing questionnaires to 100 respondents of patients at Mandaya Hospital Karawang. The results showed that the principle of hospitality services is very relevant to be implemented in the Mandaya Hospital Karawang. The implementation of these policies changed the old culture that had been used to become a new culture with the principle of hospitality. Various efforts have been made by management to anticipate changes and maximize service. Front office employees who accept changes in policies and facilities are expected to be able to provide quality services to their patients. By quantitative methods, researchers found a correlation test showed that service quality had a strong and positive effect on patient satisfaction.